FINANCIAL STRATEGY FOR A NEW ERA OF BUSINESS SUSTAINABILITY - Loso Judijanto; Rasmi; Pupung Purnamasari (Adisam Publisher, 2024)
Facing this new era, business people need to adopt business strategies that are sustainable, innovative and responsive to change. By integrating sustainable business principles, utilizing digital technology, collaborating, and focusing on employee development and understanding markets and customers, they will be able to better face challenges and achieve sustainability in their business. Managing business finances is a crucial challenge for every organization, regardless of scale or industry. In this dynamic era, where changes in technology and the business environment can occur rapidly, the right financial strategy is the foundation of sustainability. By implementing these strategies effectively, businesses can achieve sustainable success and build a strong financial foundation for future growth. The literature study approach was used to conduct the research. A survey of the literature was conducted to gather data and information about financial strategies for the new era of business sustainability. This research discusses business sustainability and new descriptions, financial strategies for business sustainability, factors that influence financial strategies for business sustainability, important issues in implementing financial strategies for business sustainability.